MENERAPKAN KONSELING ISLAMI YANG KUAT MELALUI IMPLEMENTASI RUKUN IMAN - Hermayesi, Hermayesi; Zaini, Hasan; Irman, Irman (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This Islamic counseling approach aims to provide holistic solutions for individuals facing psychological, emotional, and spiritual problems. This article aims to explore the implementation of the Pillars of Faith in Islamic counseling and its impact on the psychological well-being of Muslim individuals. This study used a qualitative approach with a case study design, involving 15-20 Muslim individuals who had participated in an Islamic counseling program. Data were collected through semi-structured interviews and observations, then analyzed using thematic analysis methods. The findings indicate that the implementation of the Pillars of Faith in Islamic counseling has a positive impact on participants' spiritual beliefs, peace of mind, and ability to deal with problems. The majority of participants reported improved mental and emotional well-being, as well as the ability to accept life's trials better. This article makes an important contribution to understanding how the integration of the Pillars of Faith in Islamic counseling practice can strengthen a more holistic and relevant counseling approach for the Muslim community, as well as address the challenges faced by counselors in their practice.